Pengaruh Media Permainan Monopoli terhadap Hasil Belajar Siswa dalam Pembelajaran IPS Gugus 15 Kota Bengkulu - Yela Purnama Sari; Herman Lusa; Ansyori Gunawan (Universitas Bengkulu, 2019)
This study aimed to find the effect of using monopoli game media towards learning result on social science major at fourth grade of SDN Gugus 15 Kota Bengkulu. This research is quantitative, using experiment method, with The Matching Only Pretest-Posttest Control Group Design. The instrument used was test sheet in multiple choice form. The test was taken two times, before and after giving treatening to the sample class. The sample in this research was the students in IVB of SDN 76 Kota Bengkulu (control group) and the students in IV of SDN 104 Kota Bengkulu (experimental group). The t value gotten was (3,668) > ttable (1,668). The result of t value was higher than t table, so it can be concluded that there are significant effect of using monopoli game media towards learning result on social science major at fourth grade SDN Gugus 15 Kota Bengkulu.